2017
DOI: 10.1136/heartasia-2016-010862
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic burden of hospitalisation for congestive heart failure among adults aged ≥19 years in the Philippines

Abstract: There were 16 cases of heart failure for every 1000 Filipino patients admitted due to a medical condition in 2014. Hypertension was possibly the most common aetiologic factor. Compared to western and Asia-Pacific countries, the local mortality rate was relatively higher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Risk factors assessed in the NNS include hypertension, obesity, high cholesterol, and diabetes [6]. In 2014, there were 16 for every 1000 Filipino patients admitted due to a medical condition wherein hypertension was possibly the most common etiology factor [7]. Moreover, in the past decade it has been observed that there is a steady increase in the prevalence of high fasting blood glucose (FBG) from 3.4% in 2003 to 5.6% in 2013, and the prevalence is even higher among Filipino adults residing in urban areas (6.4%).…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors assessed in the NNS include hypertension, obesity, high cholesterol, and diabetes [6]. In 2014, there were 16 for every 1000 Filipino patients admitted due to a medical condition wherein hypertension was possibly the most common etiology factor [7]. Moreover, in the past decade it has been observed that there is a steady increase in the prevalence of high fasting blood glucose (FBG) from 3.4% in 2003 to 5.6% in 2013, and the prevalence is even higher among Filipino adults residing in urban areas (6.4%).…”
Section: Introductionmentioning
confidence: 99%
“…In the Philippines, at least one companion/relative stays with the patient during the hospitalisation period, resulting to the said companion’s income loss. The mean age of the patients with CHF in the study was 52.6±15 years, with 48% of the study population in the 40–59 years age group,12 hence the following assumptions were used: (A) only the caretaker is economically productive; (B) both the caretaker and patient are economically productive; however, since the patient has CHF, even if he improved on discharge, he might not be 100% economically productive, hence the assumption of 50% economic productivity.…”
Section: Methodsmentioning
confidence: 99%
“…The reference time period was 2014 since the data for the prevalence of CHF hospitalisation12 was for 2014. The costs were expressed in Philippine peso (PHP) and converted to US dollars (US$) using the 2014 average conversion rate of PHP44.40 to US$1.00 18.…”
Section: Methodsmentioning
confidence: 99%
“…Risk factors assessed in the NNS include hypertension, obesity, high cholesterol, and diabetes [5]. In 2014, there were 16 for every 1000 Filipino patients admitted due to a medical condition wherein hypertension was possibly the most common etiology factor [6]. Moreover, in the past decade it has been observed that there is a steady increase of the prevalence of high fasting blood glucose (FBG) from 3.4% in 2003 to 5.6% in 2013, and the prevalence is even higher among Filipino adults residing in urban areas (6.4%).…”
Section: Introductionmentioning
confidence: 99%